Root-knot nematodes, a growing problem for Conilon coffee in Espírito Santo state, Brazil - Barros, A.F.; Oliveira, R.D.L.; Lima, I.M.; Coutinho, R.R.; Ferreira, A.O.; Costa, A. (Crop protection, 2014)
Root-knot nematodes (Meloidogyne spp.) are non-quarantine pests that are subject to regulations in Brazil because they are limiting to coffee production and easily spread by planting infected seedlings. Containing their dissemination requires knowledge of their distribution in coffee-producing areas in order to establish phyto-sanitary measures. The object of this work is to evaluate the distribution of Meloidogyne spp. in Coffea spp. in Espírito Santo state, where coffee growing is expanding. Soil and root samples were collected in Coffea arabica and Coffea canephora Conilon. Identification of Meloidogyne spp. was carried out by esterase isoenzyme phenotype and by the host range. In Espírito Santo, Meloidogyneincognita, Meloidogyne exigua, and Meloidogyne paranaensis were identified. Phenotypes I1 and I2 of M. incognita were present in 21% of all the sampled properties. This species was found mainly in the Serrana region and north of the state, and principally in plantations of C. canephora. Only phenotype E1 of M. exigua was detected, distributed in 23.8% of the properties and only in plantations of C. arabica. M. exigua was found in all the municipalities sampled in the southern region of the state and in 66.6% of the municipalities of the Serrana region. M. paranaensis, phenotype P1, was detected only in the northern region, and in 100% of the properties sampled in Baixo Guandu municipality. The study was complemented by sampling in the Zona da Mata region of Minas Gerais state, where only M. exigua, phenotype E1, was found in C. arabica plantations. M. exigua was detected in all the sampled municipalities except Paula Cândido. The populations were subjected to differential host plant tests to determine the physiological races. Races 1 and 2 of M. incognita and M. exigua were found in Espírito Santo state, and race 2 of M. exigua in Zona da Mata in Minas Gerais state. The presence of the three most important root-knot nematodes in coffee plants in Espírito Santo state indicates the need to establish measures that will contain their dissemination. •Meloidogyne dangerous species on coffee crop in ES/Brazil without sanitary measure suitable.•Wide dissemination of three important species of root-knot nematodes on coffee.•Need to establish regulatory measures in uncontaminated areas.